Unterirdischer Zentrenausbau in japanischen Städten - Schöller, Peter (ERDKUNDE, 1976)
The pre-conditions for the construction of many new centres in the underground area of Japanese cities were the increased development of the underground railway system, the multifunctional utilization of large basements in office buildings, as well as the installation of subterranean pedestrian passages. Distinct influences are also discernible in the level and dynamics of ground prices at the surface and the particular difficulties of urban reconstruction. In this underground 4 main types of centre construction are distinguished: 1. The passage type, intended for through-traffic and access to stations; 2. The supplementary type, with its retail and restoration premises intended to supplement surface locations; 3. The secondary-centre type, containing a mixed location community with departmental stores and private basements; 4. The main-centre type, catering for target-traffic by displaying a complexes supply of specialities and luxuries, departmental stores, refreshment and parking facilities. The Japanese underground centres are counted among the best and most rationally laid-out retail and restaurant facilities on earth. They are, however, purely commercial, offering neither cultural or social facilities nor any starting point for communication and urban identification. In 1974 the problems of disaster prevention and over-concentration led to increased governmental control.